Baicalein induces apoptosis and autophagy of breast cancer cells via inhibiting PI3K/AKT pathway in vivo and vitro - Yan W; Ma X; Zhao X; Zhang S (Dove Medical Press, 2018)
Wanjun Yan, Xingcong Ma, Xiaoyao Zhao, Shuqun Zhang Department of Oncology, The Second Affiliated Hospital, Xi’an Jiaotong University, Xi’an, China Purpose: Baicalein, a widely used Chinese herbal medicine, has shown anticancer effects on many types of human cancer cell lines. However, little is known about the underlying mechanism in human breast cancer cells. In this study, we examined the apoptotic and autophagic pathways activated following baicalein treatment in human breast cancer cells in vitro and in vivo.Materials and methods: In in vitro study, we used MTT and clone formation assay to confirm the inhibitory role of baicalein on proliferation of MCF-7 and MDA-MB-231 breast cancer cells. Apoptosis was detected employing Hoechst 33258 staining, JC-1 staining, and flow cytometry. Autophagy was monitored by acridine orange staining and transmission electron microscopy observation. Quantitative real-time PCR and Western blot analysis were employed to study the effects of baicalein on PI3K/AKT signaling components of MCF-7 and MDA-MB-231 breast cancer cells. In in vivo study, the effect of baicalein was tested with a breast cancer cells transplantation tumor model.Results: Our study showed that baicalein has the potential to suppress cell proliferation, induce apoptosis and autophagy of breast cancer cells in vitro and in vivo. Furthermore, baicalein significantly downregulated the expression of p-AKT, p-mTOR, NF-κB, and p-IκB while enhancing the expression of IκB in MCF-7 and MDA-MB-231 cells. It also decreased the p-AKT/AKT and p-mTOR/mTOR ratios.Conclusion: Our study demonstrated that baicalein induces apoptosis and autophagy of breast cancer cells via inhibiting the PI3K/AKT signaling pathway in vivo and vitro. Our study revealed that baicalein may be a potential therapeutic agent for breast cancer. Keywords: baicalein, breast cancer, apoptosis, autophagy, PI3K, AKT